2021
DOI: 10.1002/slct.202002108
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation to Methanol on ZnO/ZrO2 Catalysts: Effects of Zirconia Phase

Abstract: ZnO/ZrO2 samples were obtained by impregnation ZnO on three different ZrO2 polymorphic phases: monoclinic, tetrahedral and amorphous. The catalysts were tested for CO2 hydrogenation to methanol and the structure was determined using nitrogen physisorption, scanning electron microscope (SEM), Fourier transform infrared (FT‐IR) pyridine adsorption, hydrogen temperature‐programmed desorption (H2‐TPD), CO2‐TPD and X‐ray photoelectron spectroscopy (XPS). The results showed that the ZnO/tm‐ZrO2‐500 catalyst, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[15] On the other hand, during CO2 TPD measurements, two bands were observed at ~ 314 °C and 480 °C for ZrO2-t-based catalysts, but no bands were observed for the ZrO2-m-based samples, which suggests that ZrO2-t had stronger basic sites for CO2 adsorption (Figure S2b). [16] H2-TPR experiments showed comparable reduction temperatures for ZnO/ZrO2-t and ZnO/ZrO2-m, with a peak of H2 consumption between 300 and 400 °C (Figure S2c). However, the amount of hydrogen consumed in ZnO/ZrO2-m (404.79 μL) was much higher than that of ZnO/ZrO2-t (142.15.79 μL), suggesting that the highly dispersed ZnO in ZnO/ZrO2-t is less reducible due to stronger interaction with ZrO2-t.…”
Section: Resultsmentioning
confidence: 86%
“…[15] On the other hand, during CO2 TPD measurements, two bands were observed at ~ 314 °C and 480 °C for ZrO2-t-based catalysts, but no bands were observed for the ZrO2-m-based samples, which suggests that ZrO2-t had stronger basic sites for CO2 adsorption (Figure S2b). [16] H2-TPR experiments showed comparable reduction temperatures for ZnO/ZrO2-t and ZnO/ZrO2-m, with a peak of H2 consumption between 300 and 400 °C (Figure S2c). However, the amount of hydrogen consumed in ZnO/ZrO2-m (404.79 μL) was much higher than that of ZnO/ZrO2-t (142.15.79 μL), suggesting that the highly dispersed ZnO in ZnO/ZrO2-t is less reducible due to stronger interaction with ZrO2-t.…”
Section: Resultsmentioning
confidence: 86%
“…[79] The opposite shift is observed for ZrO 2 -ZnO, where the Zr 3d and Zn 2p levels appear at higher binding energies, consistent with our observations. [80] The XPS analysis reveals that the deconvoluted Zn 2p 3/2 components ratio is close to unity and does not differ between the powders. From the relative intensities of Zr 3d doublets, approximately half of the surface comprises nonstoichiometric ZrO 2 , which does not change with the annealing conditions.…”
Section: Determination Of the Element Oxidation Statementioning
confidence: 83%
“…Through comparison of amorphous, monoclinic and tetrahedral zirconia, it was observed that a monoclinic-tetragonal mix was beneficial for the reactivity. 230 The differences are attributed to the lattice oxygen content. From a mechanistic point of view, the RWGS pathway is favoured on this kind of catalyst with carbonates and bicarbonates as key intermediates.…”
Section: Co2 To Methanolmentioning
confidence: 99%